A problematic animal fossil from the early Cambrian Hetang Formation, South China. (November 2019) - Tang, Qing; Hu, Jie; Xie, Guwei; Yuan, Xunlai; Wan, Bin; Zhou, Chuanming; Dong, Xu; Cao, Guohua; Lieberman, Bruce S.; Leys, Sally P.; Xiao, Shuhai
Abstract: The lower-middle Hetang Formation (Cambrian Stage 2–3) deposited in slope-basinal facies in South China is well known for its preservation of the earliest articulated sponge fossils, providing an important taphonomic window into the Cambrian Explosion. However, the Hetang Formation also hosts a number of problematic animal fossils that have not been systematically described. This omission results in an incomplete picture of the Hetang biota and limits its contribution to the understanding of the early evolution of animals. Here we describe a new animal taxon, Cambrowania ovata Tang and Xiao, new genus new species, from the middle Hetang Formation in the Lantian area of southern Anhui Province, South China. Specimens are preserved as carbonaceous compressions, although some are secondarily mineralized. A comprehensive analysis using reflected light microscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and micro-CT reveals that the new species is characterized by a spheroidal to fusoidal truss-like structure consisting of rafter-like crossbars, some of which are secondarily baritized and may have been internally hollow. Some specimens have aperture-like structures that are broadly similar to oscula of sponges, whereas others show evidence of a medial split reminiscent of gaping carapaces. While the phylogenetic affinity of Cambrowania ovata Tang and Xiao, n. gen. n. sp. remains problematic, we propose that it may represent carapaces of bivalved arthropods or more likely sponges in early life stages. Along with other problematic metazoan fossils such as hyolithids and sphenothallids, Cambrowania ovata Tang and Xiao, n. gen. n. sp. adds to the diversity of the sponge-dominated Hetang biota in an early Cambrian deepwater slope-basinal environment. UUID:http://zoobank.org/44de9472-7e3f-42d1-9554-7b3434df91d9